Analyzing The Impact of Motivational Drivers on User ‎Satisfaction in Online Gaming, with The Mediating Factor User ‎Addiction - Rani , S. Dilli; Selvasundaram, K. (International Journal of Accounting and Economics Studies, 2025)
This study explores the impact of gaming motivations on user satisfaction through the mediating factor of user addiction in online gaming. ‎Immersion, achievement, escapism, socialization, competition, cognition, and earning, seven motivational factors used as independent ‎factors and analyzed. These factors were used as a first order construct and were studied under a second order construct motivational factor ‎a second order construct. Data were collected using snowball sampling techniques from 272 online gamers, and mediation analysis was ‎performed to test the proposed model. The findings reveal that while motivational factors were directly influencing satisfaction, addiction ‎acts as a mediating mechanism that reinforces this impact. Through Rationality Addiction Theory, the outcomes suggest that players ‎integrate addictive engagement as part of their satisfaction-maximization. The research further highlights wider economic and policy ‎implications, specifically the role of motivational factors in industrial revenue models and the need for sensible gaming structures to balance ‎user satisfaction and societal well-being‎.
Keywords: Online Games; User Addiction; User Satisfaction; Rationality Theory